ANALISIS PASAR KERJA KABUPATEN BANYUWANGI - Andri Wijanarko (MediaTrend, 2014)
The quality of human resources is to determine a person's activities in theeconomy to earn income. While the number of working age population by level ofeducation is higher but still unemploy, it should be brought to the attention of allparties concerned that higher education alone has not been enough to prepare the jobsearch.Based on the data of structure of the population pyramid is dominated byyoung age, then the Government of Banyuwangi Regency should perform control ofbirth rates. A large population at a young age can occur due to improvements in thequality of health facilities for the mother and the child so that the level of infantmortality is dropping, just that it can increase the proportion of young population.When controlling the birth rate is not done, can trigger concerns did not materialize"demographic bonus", which at the national level will be achieved by 2025-2030.Based on the data of education workers that still dominated at the level of basiceducation (primary and JSS finished finished) by 54,86%, then the Office of education(Dinas Pendidikan) should improve school participation rate, i.e. by increasing thenumber of educators and school facilities adds up to the remote region.